2014
DOI: 10.1002/cphc.201402383
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Dynamics in the Lactim Tautomer of Phycocyanobilin: A Long‐Wavelength Absorbing Model Compound for the Phytochrome Chromophore

Abstract: Transient UV/Vis absorption spectroscopy is used to study the primary dynamics of the ring-A methyl imino ether of phycocyanobilin (PCB-AIE), which was shown to mimic the far-red absorbance of the Pfr chromophore in phytochromes (R. Micura, K. Grubmayr, Bioorg. Med. Chem. Lett.- 1994, 4, 2517-2522). After excitation at 615 nm, the excited electronic state is found to decay with τ1 =0.4 ps followed by electronic ground-state relaxation with τ2 =1.2 and τ3 =6.7 ps. Compared with phycocyanobilin (PCB), the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Given the difficulty to rationalize color-tuning in microbial and animal rhodopsins, which depend on the 'simpler' chromophore retinal, it is not surprising that theoretical approaches such as full-scale quantum chemical and QM/MM calculations on complex bilin chromophores in their protein environment are still in their infancy [49][50][51]. Here, progress is not only impeded by radiation effects on the chromophore during structural analyses [23 ,52], but also by intrinsic conformational heterogeneity of the P r state and [53][54][55][56] and to some extent also the P fr state [57].…”
Section: Discussionmentioning
confidence: 99%
“…Given the difficulty to rationalize color-tuning in microbial and animal rhodopsins, which depend on the 'simpler' chromophore retinal, it is not surprising that theoretical approaches such as full-scale quantum chemical and QM/MM calculations on complex bilin chromophores in their protein environment are still in their infancy [49][50][51]. Here, progress is not only impeded by radiation effects on the chromophore during structural analyses [23 ,52], but also by intrinsic conformational heterogeneity of the P r state and [53][54][55][56] and to some extent also the P fr state [57].…”
Section: Discussionmentioning
confidence: 99%
“…Several models have been proposed to produce a redshift to the far-red region based on spectroscopic and computational studies using model compounds (62)(63)(64)(65). Stanek and Grubmayr demonstrated that a deprotonated ring A lactim anion led to a significant redshift in the long-wavelength band (64).…”
Section: Far-red-absorbing Mechanisms In Fr-cbcrsmentioning
confidence: 99%
“…Stanek and Grubmayr demonstrated that a deprotonated ring A lactim anion led to a significant redshift in the long-wavelength band (64). Diller and colleagues proposed that far-red absorption involves a D-ring lactim tautomer (65). Krois showed that a fully protonated bilin exhibited a redshift, which was further enhanced by bringing close two carbonyls in a constrained all-Z,syn model compound (62).…”
Section: Far-red-absorbing Mechanisms In Fr-cbcrsmentioning
confidence: 99%
“…Upon red‐light absorption the Pr chromophore undergoes a rapid Z / E isomerization at the C15 methine bridge, finally resulting in a ZZEssa stereochemistry of the Pfr chromophore . Both primary light induced reactions involve several excited‐state intermediates and evolve on a picosecond time scale, typically with a “slow” Pr reaction (30–100 ps or longer) and a “fast” Pfr reaction (a few ps) . The photoinduced Pr half‐cycle is characterized by the first electronic ground‐state intermediate lumi‐R (already in ZZE configuration) with red‐shifted absorption spectrum and consecutive, thermally driven reaction steps on the μs‐to‐ms time scale involving meta ‐Ra, meta ‐Rc and finally Pfr .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] Both primary light induced reactions involve several excited-state intermediates and evolve on ap icosecond time scale, typically with a" slow" Pr reaction (30-100 ps or longer) [20][21][22][23][24][25][26][27][28][29][30][31] and a" fast" Pfr reaction (a few ps). [20,21,23,30,[32][33][34] The photoinduced Pr half-cycle is characterizedb yt he first electronic ground-state intermediate lumi-R (already in ZZE configuration) with red-shifted absorption spectrum and consecutive, thermally driven reaction steps on the ms-to-ms time scale involving meta-Ra, meta-Rc and finally Pfr. [35,36] Previous Bathy phytochrome Agp2f rom Agrobacteriumf abrum exhibits an unusually low pK a = 7.6 in the Pr state in contrast to ap K a > 11 in the Pfr state, indicating ap H-dependent charge distribution and H-bond network in the Pr chromophoreb inding pocket around neutralp H. Here, we report on ultrafast UV/ Vis absorption spectroscopy of the primary Pr photoisomerization of Agp2 at pH 6a nd pH 9a nd upon H 2 O/D 2 Ob uffer exchange.…”
Section: Introductionmentioning
confidence: 99%